2021
DOI: 10.1186/s13059-021-02425-9
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of temperature adaptation is shaped by population ancestry and not by selection regime

Abstract: Background Understanding the genetic architecture of temperature adaptation is key for characterizing and predicting the effect of climate change on natural populations. One particularly promising approach is Evolve and Resequence, which combines advantages of experimental evolution such as time series, replicate populations, and controlled environmental conditions, with whole genome sequencing. Recent analysis of replicate populations from two different Drosophila simulans founder populations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 110 publications
1
14
2
Order By: Relevance
“…This observation is highly consistent with a series of publications, which focused on laboratory adaptation in Drosophila subobscura and found strong phenotypic and genomic responses [70,77]. The abundant evidence for laboratory adaptation in this study contrasts the observation of an E&R study in D. simulans , which found no shared haplotype block moving in the same direction between hot and cold temperatures [66].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is highly consistent with a series of publications, which focused on laboratory adaptation in Drosophila subobscura and found strong phenotypic and genomic responses [70,77]. The abundant evidence for laboratory adaptation in this study contrasts the observation of an E&R study in D. simulans , which found no shared haplotype block moving in the same direction between hot and cold temperatures [66].…”
Section: Discussionsupporting
confidence: 92%
“…direction differs from an E&R study in Drosophila simulans, which found no shared haplotype block that was selected in the opposite direction in hot and cold environments [66].…”
Section: Discussioncontrasting
confidence: 89%
“…In an attempt to shed more light on this different behaviour, replicate populations from the same Portuguese founder population were studied for approximately the same number of generations in a cold selection regime (10–20°C) [ 35 ]. Interestingly, the genomic response at the cold temperature was also highly parallel, similar to the hot temperature regime [ 28 ].…”
Section: The Degree Of Parallelism Depends On the Founder Population ...mentioning
confidence: 99%
“…Subtle shifts of allele frequencies across the genome can lead to divergent genomic backgrounds that give populations access to different ecological niches (e.g. [ 47 , 48 ]).…”
Section: Discussionmentioning
confidence: 99%